KAJIAN MUSIKOLOGI RAGAM POLA TABUHAN TRADISIONAL TAR DI KELURAHAN SUNGAI JAWI DALAM KOTA PONTIANAK - Angga Khasbullah; Ismunandar Ismunandar; Asfar Muniir (Universitas Tanjungpura, 2019)
AbstractThe background of this research way there are so many pattern tradisionaltar in Kelurahan Sungai Jawi Dalam Kota Pontianak which is not written yet in the west notation. There is uniqueness in that pattern of traditional percussion instrument whether it is musical aspect in terms of the textual or arts performance aspect in terms of the contextual. The problem of this research is the technique of how to play “tar” and how the pattern of traditional percussion instrument in Pontianak city.The method of this research way descriptive with qualitative method and musicology approach. The resource data of this research way the informant who knows and understandsabout every kind of pattern of traditional percussion instrumentin Kelurahan Sungai Jawi Dalam Kota Pontianak.The data collection technique of this research is observation, interview, and documentations.The result this research way there are twenty pattern of traditional percussion of tar in Kelurahan Sungai JawiDalam Kota Pontianak that is used to escort the art of Hadrah which consist of three stages; they are Gencat, Terosan, and Marade. This research is to describe each of the kind of pattern of traditional percussion which has the design percussion pattern that is shaped by the literal repeating. Keywords: Pattern of Traditional Percussion Instrument, Tar, Hadrah